Crossing the Ideological Divide? Egypt's Salafists and the Muslim Brotherhood after the Arab Spring. (2nd June 2016) - Ranko, Annette; Nedza, Justyna
ABSTRACT: An important strand in the literature has stressed the analytical distinction between the Muslim Brotherhood's brand of Islamism and the Salafist movement. This article examines the shifts that have occurred within these two movements in Egypt since the Arab Spring. It specifically asks whether approximations between them in terms of strategies of actions have been paralleled by ideological approximations. The article argues that both movements have seen increased diversification which has—especially at the fringes—involved a reshaping of identities and ideological approximations that may facilitate cooperation between segments of these movements in the future.